Digital Democracy, Digital Dangers: Tracing Cybercrime Victimization in Finnish Online Political Discourse - Koivula, Aki; Räsänen, Pekka; Keipi, Teo (Switzerland, 2025)
This study investigates the relationship between online political engagement, political preferences, and cyberhate victimization in a Nordic country. We utilize longitudinal, population-level data from over 3,750 Finnish respondents surveyed between 2017 and 2021. The data affords a nuanced understanding of cyberbullying victimization trends over time and how such victimization reflects the respondents’ online behavior. The findings reveal a notable association between experiencing cyberhate and the respondents’ political activity, highlighting the polarizing nature of the online political environment in Finland. The data indicates also that left-wing supporters are disproportionately targeted by online hate. The study raises concerns about the urgent need for effective measures to mitigate the impact of cyberhate, toward more respectful online discourse among individuals with differing political beliefs.
HCI International 2024 Posters : 26th International Conference on Human-Computer Interaction, HCII 2024, Washington, DC, USA, June 29 – July 4, 2024, Proceedings, Part VI